Accounting for continuous species' responses to management effort enhances cost-effectiveness of conservation decisions. (May 2016) - Cattarino, Lorenzo; Hermoso, Virgilio; Bradford, Lindsay W.; Carwardine, Josie; Wilson, Kerrie A.; Kennard, Mark J.; Linke, Simon
Abstract: Limited resources available for conservation require prioritizing location and level of conservation management efforts to abate threats to species. Ideally, the optimal level of management effort to allocate to an action should be informed by the species' responses to actions. This would enhance cost-effectiveness of conservation recommendations. How continuous species' responses to varying levels of management effort ('species response curves') affect the cost of abating threats to species is poorly understood, but critical for cost-effective threat management. We developed an optimization approach to prioritize management efforts based on varying species' response curves. We tested our framework in the Mitchell River catchment, northern Australia, to find the optimal level of effort to allocate to restoration of river connectivity and riparian revegetation to improve persistence of freshwater fish species. We compared the results of our analysis against a traditional approach, which assumes that (1) an action is either fully implemented or not; and (2) when the action is fully implemented the species persists; when the action is not implemented, the species goes locally extinct. We showed that by using species response curves we can abate threats to species at budgets up to 20% lower than when applying the traditional approach. Our approach can aid identifying how much effort (i.e., area managed, timeframe of management or budget invested) to allocate to multiple actions, and where, to cost-effectively abate threats to species. This has the potential to significantly improve biodiversity outcomes when resources are limited, by improving precision of on-ground conservation decisions. Highlights: We present a new framework for priority threat management based on species responses to continuous levels of effort. Our approach achieves species conservation targets at costs up to 20% lower than when response curves are ignored. Our approach allows precise prescription of conservation effort, thus improving cost-effectiveness of resource allocation.